Nucleation and stability of skyrmions in three-dimensional chiral nanostructures - Yan Liu (Nature Portfolio, 2020)
Abstract We studied the magnetization evolution in three-dimensional chiral nanostructures, including nanotubes and circularly curved thin films, by micromagnetic simulations. We found that in a nanotube skyrmions can be formed by broken of the helical stripes on the left and right sides of the nanotube, and the formation of skyrmions doesn’t correspond to any abrupt change of topological number. Skyrmions can exist in a large range of magnetic field, and the thinner nanotube has a larger field range for skyrmion existence. The configuration of a skyrmion in nanotubes is different from the one in thin film. From the outer to the inner circular layer, the size of the skyrmion becomes larger, and the deformation becomes more obvious. In circularly curved magnetic films with fixed arc length, there are three kinds of hysteresis processes are found. For the curved films with a large radius, the magnetization evolution behavior is similar to the case in two-dimensional thin films. For the curved films with a small radius, the skyrmions are created by broken of the helical stripes on the left and right sides of the curved film. For the curved film with a medium radius, no skyrmion is formed in the hysteresis process.